Structural Analysis of PlyKp104, a Novel Phage Endoysin - Jung-Min Choi (Crystals)
Antibiotic resistance has emerged as a critical global public health challenge, prompting increased interest in non-antibiotic antimicrobial strategies such as bacteriophage-derived endolysins. Although endolysins possess strong lytic potential, their application to Gram-negative bacteria remains limited due to the outer membrane barrier. PlyKp104 is a recently identified phage-derived endolysin that exhibits lytic activity against Gram-negative bacteria without the aid of membrane permeabilizers. In this study, the crystal structure of PlyKp104 was determined at a resolution of 1.85 Å. PlyKp104 consists solely of a catalytic SLT domain, and structure-based analysis revealed a putative active site and key structural features associated with substrate binding. Comparative analysis with homologous structures suggested that PlyKp104 belongs to lytic transglycosylase family 1. B-factor analysis and hydrophobic interaction mapping indicated that the domain exhibits high structural stability, supported by conserved hydrophobic residues clustered in motifs I and II. During structure determination, an unidentified electron density was consistently observed near a neutral, hydrophobic surface region. Its shape and environment suggest the presence of a lipid-like molecule, implying a potential lipid-binding site. These findings provide structural insight into PlyKp104 and contribute to the understanding of endolysin mechanisms against Gram-negative bacteria, with implications for future protein engineering efforts.